2006
DOI: 10.1182/blood-2006-04-017467
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immunity is the dominant barrier for allogeneic bone marrow engraftment in sensitized recipients

Abstract: We evaluated the relative contribution of the humoral and cellular arms of the immune response to bone marrow cells transplanted into sensitized recipients. We report here for the first time that humoral immunity contributes predominantly to allosensitization. Although the major role for nonmyeloablative conditioning is to control alloreactive host T cells in nonsensitized recipients, strikingly, none of the strategies directed primarily at T-cell alloreactivity enhanced engraftment in sensitized mice. In eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 33 publications
3
59
1
Order By: Relevance
“…10 Rejection is a major cause of graft failure and is caused by recipient T cells, natural killer (NK) cells, or Abs. [10][11][12][13][14][15] An increase in number of residual host T cells is associated with graft rejection in pediatric allogeneic transplantation. 16 HLA-C mismatch with NK epitope mismatching in the rejection direction are associated with higher rates of graft rejection after HLAmismatched transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…10 Rejection is a major cause of graft failure and is caused by recipient T cells, natural killer (NK) cells, or Abs. [10][11][12][13][14][15] An increase in number of residual host T cells is associated with graft rejection in pediatric allogeneic transplantation. 16 HLA-C mismatch with NK epitope mismatching in the rejection direction are associated with higher rates of graft rejection after HLAmismatched transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In patients receiving major HLA-Ag mismatched allo-SCT, a positive crossmatch has been significantly correlated to increased risk for graft failure and inferior survival as compared with patients transplanted against a negative crossmatch. 9,10 Taken together, on the basis of the above-mentioned publications, we have on a regular basis performed cytotoxic crossmatches in allo-SCT patients before transplantation since 2000.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, recent data from mouse models indicate that the presence of preformed donor-reactive Abs is a dominant barrier for BM engraftment in allosensitized recipients. 7,8 In contrast to organ transplantation, data on the clinical outcome after allo-SCT across a positive crossmatch are scarce. Previous work by Anasetti et al 9 showed that patients with a positive crossmatch had a significantly increased risk of rejection compared with patients with a negative crossmatch.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with early reports that the majority of hematopoietic progenitor cells co-express HLA-DR 45,46 and that CD4 + T cells recognizing mismatched HLA-DR Ag can be associated with graft failure. 47 Recently, some animal studies suggest that humoral immunity is the major barrier to engraftment, 48,49 although cellular immunity has been recognized as the primary mechanism of rejection. 7 In this study, we could not determine whether humoral or cellular immunity would be a dominant barrier to engraftment.…”
Section: Discussionmentioning
confidence: 99%